Unusual 28, 29-nor-9, 19 cycloartane triterpenoids from Chinese medical plant Streptocaulon griffithii Hook. (December 2017) - Ge, Yi-Chao; Cheng, Yu-Chun; Wang, Kui-Wu; Wang, Hong
Graphical abstract: Highlights: Eight triterpenoids were isolated from Streptocaulon griffithii . Their structures were identified by spectroscopic analysis. Compunds 1–3 were novel compounds with anti-tumor activity. The results might helpful for explaining the use of S. griffithii in TCM. Triterpenes may be useful as potential chemotaxonomic markers of Streptocaulon genus. Abstract: Phytochemical investigation of the root of Streptocaulon griffithii Hook (Asclepiadaceae) led to the isolation of three unusual novel triterpenoids, 28, 29-nor-3 β, 4 β -dihydroxyl-9, 19-cycloartan-26-acid (1 ), 28, 29-nor-3 β, 4 β -dihydroxyl-9, 19-cycloartan- 26-acid methylester (2 ), a 30-nor-lupeol derivative 30-nor-3 β - acetoxy-lupan-20-one (3 ) and five known compounds4 –8 . Their structures were established on the basis of physical and spectroscopic analysis, including 1D and 2D NMR (1 H, 13 C, COSY, HSQC, and HMBC), ESI mass spectrometry, and by comparison with the NMR data published in the literature. The cytotoxicities of the isolated compounds against a panel of cultured tumor cell lines (Hela, PC3, SMMC7721, CNE) were evaluated. The new compounds1 and2 showed moderate activities with IC50 values of 11.76 ∼ 26.52  μ g/mL, respectively. The result showed that triterpenoids are typical compounds of Streptocaulon genus, which could be useful as characteristic markers in chemotaxonomic research and might helpful for explaining the use of S. griffithii in traditional medicine.